2021
DOI: 10.1371/journal.pone.0257036
|View full text |Cite
|
Sign up to set email alerts
|

Research on the impact of COVID-19 on Chinese small and medium-sized enterprises: Evidence from Beijing

Abstract: COVID-19 leads small and medium-sized enterprises (SMEs) to survive very hard. The development difficulties of SMEs lead to weak employment and GDP growth in various countries. In the process of COVID-19’s continuous spread, what is the major reason for the difficulties of SMEs? This paper hopes to answer this question by studying SMEs in Beijing. On this basis, this paper uses structural equation model (SEM) to study the relatively fast recovery of SMEs in Beijing, China, to explore the factors affecting SMEs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 47 publications
2
39
0
1
Order By: Relevance
“…Lu et al (2021) surveyed 4,807 SMEs in China and found how the pandemic presented a huge existential challenge for SMEs impacting the resumption of work, income, and confidence with day-to-day operation. Ma et al (2021) similarly conducted a survey with 234 SMEs from various industries in Beijing to study the specific challenges from COVID-19. They studied the pandemic's impact from four perspectives: financing activities, markets, employees, and costs.…”
Section: Covid-19 Risks and Opportunities For Businessesmentioning
confidence: 99%
“…Lu et al (2021) surveyed 4,807 SMEs in China and found how the pandemic presented a huge existential challenge for SMEs impacting the resumption of work, income, and confidence with day-to-day operation. Ma et al (2021) similarly conducted a survey with 234 SMEs from various industries in Beijing to study the specific challenges from COVID-19. They studied the pandemic's impact from four perspectives: financing activities, markets, employees, and costs.…”
Section: Covid-19 Risks and Opportunities For Businessesmentioning
confidence: 99%
“…The COVID-19 pandemic has affected the business activities of enterprises all around the world, causing pressures such as decreased customer demand, production stagnation, disruptions in supply chains and increased uncertainty [1,2]. Small businesses have been particularly affected, as they typically have fewer human, financial and technical resources compared to larger businesses [3].…”
Section: Introductionmentioning
confidence: 99%
“…A high default risk ratio and low credit-ratings of small and medium-sized enterprises (SMEs) is a common issue across both developed and developing economies (Taghizadeh-Hesary et al, 2021 ). Especially, as the COVID-19 pandemic continues to spread and rebound, the financing pressure of SMEs is further intensified (Ma et al, 2021 ; Calabrese et al, 2022 ). To alleviate SMEs' financial constraints, Credit Guarantee Schemes (CGSs) have been widely proposed and used around the world (Cowling et al, 2018 ; Song et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%